2020
DOI: 10.1080/09273972.2020.1767480
|View full text |Cite
|
Sign up to set email alerts
|

Instead of pulley bands, does retrobulbar fat keep the eye muscle bellies in place and thereby act like a pulley?

Abstract: Extraocular muscle pulley bands were described by Tenon in 1805 as "faisceaux tendineux" acting as "poulies de renvoi." The Passive and Active Pulley Hypotheses propose that these connective-tissue bands between muscle and bony orbital rim limit vertical shift of the horizontal rectus muscle belly in up-and downgaze, caused by the muscle's tendency to assume the shortest path from origin to insertion. The band's attachment to the muscle moves 20 mm sagittally when the eye looks from 50°left to 50°right, howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The EOMs are surrounded by orbital fat, which helps to stabilize the muscle path. 57 , 58 Studies have shown that the orbital fat can be deformed with changes in eye position despite its low elasticity and viscosity. 59 Such deformation of the orbital fat could lead to systematic passive changes in cross-section of the surrounded EOM, and perhaps misinterpreted as changes in muscle contractility.…”
Section: Discussionmentioning
confidence: 99%
“…The EOMs are surrounded by orbital fat, which helps to stabilize the muscle path. 57 , 58 Studies have shown that the orbital fat can be deformed with changes in eye position despite its low elasticity and viscosity. 59 Such deformation of the orbital fat could lead to systematic passive changes in cross-section of the surrounded EOM, and perhaps misinterpreted as changes in muscle contractility.…”
Section: Discussionmentioning
confidence: 99%
“…The rectus EOMs course anteriorly through the orbital fat until they enter their connective tissue pulleys that ensheath them as they penetrate posterior Tenon's fascia (Figure 1). Contrary to what is described, there is no "muscle cone" of connective tissue among the adjacent rectus EOM bellies in the mid-to-deep orbit (Figure 1; Simonsz, 2020). The rectus muscles insert into the sclera anteriorly to the globe's equator.…”
Section: Gross Anatomy Of the Extraocular Musclesmentioning
confidence: 82%
“…The retrobulbar fat and its enveloping connective-tissue sheets limit the sideways shift of rectus muscle bellies in eye movements out of the plane of the muscle. They are well capable of keeping it in place [ 29 ]. It was clear from these specimens that the connective septa between the lateral rectus muscle belly and the posterior periorbita are loose and not very dense, so it seems unlikely that they will significantly affect this issue.…”
Section: Discussionmentioning
confidence: 99%